Evaluation of hybrids developed from diversified CMS lines for resistance to powdery mildew in sunflower (Helianthus annuus L.) - Nandini, C.; Shadakshari, Y.G.; Karuna; K.Puttarangaswamy, K.T. and; DattatrayaBhat (Electronic Journal of Plant Breeding, 2016)
Two ninety two hybrids developed from crossing six diversified Cytoplasmic Male Sterile (CMS) lines viz., ARG-2-1-2, ARG 6-3-1-4, MUT2-8-3-2, ARG 3, PKUZ and PRUN 29 with 40 inbred lines. Hybrids were evaluated for powdery mildew resistance reaction. Among 292 hybrids screened, none of the hybrids were highly resistant to powdery mildew, 33 hybrids were resistant, 37 were moderately resistant, 95 were susceptible and 126 showed highly susceptible reaction. More number of hybrids developed from PRUN 29 line was found more resistant to powdery mildew. Out of 48 hybrids developed from PRUN 29 CMS line, 15 and 16 hybrids were found to be resistant and moderately resistant reaction. Similarly 12 and 5 hybrids developed from line ARG 6-3-1-4 showed resistant and moderately resistant reaction respectively. Hybrids developed from CMS lines ARG 2-1-2 and MUT2-8-3-2 were shown susceptible reaction. Hybrids which showed sterile reaction along with resistance to powdery mildew could be further used to develop inbreds which are resistant to powdery mildew. Hybrids which showed fertile reaction along with resistance to powdery mildew will be evaluated in multilocation and multiseason to identify hybrids which are high yielding coupled with resistance to powdery mildew disease.